1995
DOI: 10.1254/jjp.68.423
|View full text |Cite
|
Sign up to set email alerts
|

Effects of GABAergic Drugs on the Recovery of Reflex Potentials after Spinal Cord Ischemia in Cats

Abstract: ABSTRACT-Effectsof GABAergic drugs on the recovery of reflex potentials after spinal cord ischemia were examined in anesthethized spinal cats. Monosynaptic reflex (MSR) and polysynaptic reflex (PSR) potentials, elicited by electrical stimulation of the tibial nerve in spinal cats, were recorded from the Jumbo-sacral ventral root. The spinal reflex potentials were immediately depressed by occlusion of the thoracic aorta and the bilateral mammary arteries for 10 min. The potentials recovered gradually to the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Studies of the negative effects of excitatory and inhibitory neurotransmitters in spinal cord ischemia indicate that some of these effects can be antagonized by naloxone. [14][15][16][17][18][19] With the previously demonstrated predictive paraplegia model, the slope of the regression plot for estimated versus actual deficits for a particular technique of repair over time is an estimate of the paraplegia risk for that technique (Table IX and Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the negative effects of excitatory and inhibitory neurotransmitters in spinal cord ischemia indicate that some of these effects can be antagonized by naloxone. [14][15][16][17][18][19] With the previously demonstrated predictive paraplegia model, the slope of the regression plot for estimated versus actual deficits for a particular technique of repair over time is an estimate of the paraplegia risk for that technique (Table IX and Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports from our and other laboratories indicated that acute spinal ischaemia followed by reperfusion reduced the GABA level of the spinal cord probably by increasing GABA release (Homma et al, 1979;Martiniak et al, 1991;Zhang et al, 1994). Since GABA receptor stimulation inhibited the recovery of PSR potentials after spinal cord ischaemia (Suzuki et al, 1995), nicorandil and pinacidil might inhibit the depolarization-induced GABA release from spinal cord neurones and enhance the recovery of PSR potentials.…”
Section: Resultsmentioning
confidence: 71%
“…The latter (i.v. bicuculline and semicarbazide [147]) mainly restored reflex potentials after spinal cord ischemia in cats. Thus, the complex mechanism of the role in spinal cord I/R injury exists and needs further distinguishing.…”
Section: The Role Of Gaba In Spinal Cord I/r Injurymentioning
confidence: 99%